2013
DOI: 10.1055/s-0033-1345169
|View full text |Cite
|
Sign up to set email alerts
|

MiR-21 is Overexpressed in Response to High Glucose and Protects Endothelial Cells from Apoptosis

Abstract: Diabetes was an increasing public health problem nowadays. Accumulating evidences had shed a light on the involvement of endothelial cell dysfunction in the pathogenesis of diabetes-associated vascular diseases. MiR-21, a multiple-functional miRNA, was evidenced to be involved in endothelial dysfunction, however, the underlying molecular mechanisms were still unknown. In current study, we investigated the intrinsic link between miR-21 and high glucose-induced endothelial dysfunction. We demonstrated that expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…At least two microRNAs that can inhibit S100A4 have been reported: miR‐21 in endothelial cells and miR‐187‐3p in hepatocellular carcinoma . Although these studies used other cellular models, these signals may share phenomena with our miR‐124 /S100A4 in VSMCs to reduce cell survival, suggesting that these microRNAs might also play a key role in neointimal proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…At least two microRNAs that can inhibit S100A4 have been reported: miR‐21 in endothelial cells and miR‐187‐3p in hepatocellular carcinoma . Although these studies used other cellular models, these signals may share phenomena with our miR‐124 /S100A4 in VSMCs to reduce cell survival, suggesting that these microRNAs might also play a key role in neointimal proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Let-7g was reported to target caspase-3 and inhibit the apoptosis induced by oxidized low density lipoprotein (OX-LDL) in endothelial cells [83]. MiRNA-29b promotes high-fat diet-stimulated endothelial permeability and apoptosis in apoE knock-out mice by down-regulating MT1 expression [84], miR-21 is overexpressed in response to high glucose and protects endothelial cells from apoptosis by targeting death-domain associated protein [85]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate the potential mechanism of miRNAs in the pathogenesis of PDR, we searched the target genes associated with miR-21, miR-181c and miR-1179. We found that miR-21 was reported inducing tumor angiogenesis through targeting PTEN, leading to activate AKT and ERK1/2 signaling pathways, and thereby enhancing HIF-1α and VEGF expression [22], furthermore, miR-21 protected endothelial cell against high glucose-induced endothelial cytotoxicity [23]. These indicated that miR-21 was highly associated with the angiogenesis with the microenvironment of high glucose.…”
Section: Discussionmentioning
confidence: 99%